Citizen Science for Quantifying and Reducing Food Loss and Food Waste - Pateman, Rachel M.; de Bruin, Annemarieke; Piirsalu, Evelin; Reynolds, Christian; Stokeld, Emilie; West, Sarah E. (Frontiers in Sustainable Food Systems, 2020)
Food loss and food waste are urgent global problems relating to environmental and social challenges including biodiversity loss, climate change, health and malnutrition. Reduction targets have been set, including Sustainable Development Goal (SDG) 12.3, which aims to halve per capita food waste at retail and consumer levels globally by 2030, as well as reduce food losses along production and supply chains. Citizen science, the engagement of members of the public in data collection and other elements of the scientific process, can play a role in tackling the problem of food waste and food loss. In this paper, we scope opportunities for using citizen science to answer 26 priority research questions identified by experts in the field of food waste and food loss as being critical to achieving SDG12.3. We describe how citizen science can be used to quantify and understand causes of food loss and waste. Crucially, we demonstrate the value of citizen science in being not just a data gathering tool but also a method of bringing about change through influencing action, from individual behaviour to policy making. Furthermore, we argue the need to bring together all actors in the food system in citizen science projects in order to build shared understanding that will ultimately lead to reduced loss and waste across the food system.